2015
DOI: 10.1007/s13224-015-0728-3
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Low Molecular Weight Heparin Improving Perinatal Outcome in Non-thrombophilic Placental-Mediated Complications

Abstract: Objective To study the role of low molecular weight heparin (LMWH) in perinatal outcome. Methods A randomized, case control study was conducted at Safdarjang hospital, New Delhi. Patients were recruited from Sept. 2011 to May 2013 and were followed up till delivery. Thirty cases and controls were enrolled which comprised non-thrombophilic patients with previous history of preeclampsia, fetal growth restriction, abruption, and stillbirth ([20 weeks). Study group received daily single dose of LMWH depending upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The results were consistent with previous research results. Low molecular heparin can positively act on preeclampsia [ 18 , 19 ]. The p38MAPK signaling pathway has been reported to be related to the growth and migration of trophoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The results were consistent with previous research results. Low molecular heparin can positively act on preeclampsia [ 18 , 19 ]. The p38MAPK signaling pathway has been reported to be related to the growth and migration of trophoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be used in women at high risk of maternal venous‐thromboembolism. Some smaller studies show a potential benefit; one Indian study 72 showed that prophylactic LMWH commenced before 15 weeks of gestation substantially reduced admissions to the neonatal intensive care unit (NICU) by 80%. However, the EPPI 73 and TIPPS 74 studies, which were both large, multicentre, randomised controlled trials, failed to demonstrate benefit in fetal outcomes.…”
Section: Specific Pharmacological Treatmentsmentioning
confidence: 99%
“…Stricter stratification of patients into study groups, based not only on the history of pregnancy complications, but also on its association with genetic thrombophilia, showed more interesting results [35,61]. Thus, in particular, in the study of de Vries et al [35], including 139 women with hereditary thrombophilia, of which 82 (59.0% of 139) had FVL (1961) GA mutation, sodium dalteparin (daily at a dose of 5000 IU) in combination with acetylsalicylic acid (daily at a dose of 75-100 mg) led to Absolute Risk Reduction (ARR) of early-onset preeclampsia (up to 34 weeks) by 8.7% [95% CI (1.9-15.5) p =0.012].…”
Section: Partmentioning
confidence: 99%